Wildlife trafficking as a societal supply chain risk: Removing the parasite without damaging the host? - Sina Duensing; Martin C. Schleper; Christian Busse (Journal of Supply Chain Management, 2023)
Humanity's intrusion into nature—with the objective of selling animals and plants as medicine, food, and tourist attractions—is detrimental not only to biodiversity and the health of ecosystems but also to local communities, global society, and human health. Often, traffickers exploit legal supply chains to secretly move endangered species and protected wildlife to end consumers. Serendipitous discoveries of wildlife trafficking attempts raise concerns that existing efforts to prevent wildlife trafficking and other criminal exploitation of legal supply chains brought about by international laws, regulations, and voluntary initiatives may often fail. Indeed, most supply chains are designed for economic purposes such as efficiency or responsiveness rather than security. Scholarship in supply chain management has thus far dedicated scarce attention to the overarching phenomenon of illegal exploitation of otherwise legal supply chains, referred to as “supply chain infiltration.” Because we were unable to speak with perpetrators directly, we obtained insights from expert stakeholders in order to study the delicate and covert topic of what makes supply chains vulnerable to wildlife trafficking, as well as how this vulnerability can be mitigated. Our data set comprises 37 semi-structured interviews with knowledgeable stakeholders concerning wildlife trafficking, specifically in maritime supply chains. This research develops a model that explains supply-chain-related vulnerabilities to wildlife trafficking and elaborates regarding how respective actors can contribute in addressing this understudied issue. We introduce the concept of “societal supply chain risk” to refer to hazards that emanate from or materialize within supply chains, which primarily affect actors in the supply chain context—and possibly even humanity in its entirety. Our research calls for more supply chain research, exploring situations in which individual firms may not be affected but can contribute to the solution.
Keywords: 330; biodiversity; criminal supply chain; regulation; social sustainability; supply chain infiltration; supply chain risk; sustainable supply chain management; wildlife trafficking